APPLICATION OF ROBOTIC PLATFORMFOR SMALL MRCHANISATION IN MAN MADE DISASTER - Kivokurtcev, O.A. (Perm Federal Research Centre Journal, 2015)
Environmental impact of the robotic platform of small-scale mechanization for snow removal have been analyzed. The universal robotic platform has been projected at the Cars and Technological Machines department of PNRPU. The main factors affecting the environment have been tested.